Games we like - Murray, W.; Aitchison, Martin (Ladybird Books Loughborough [England], 1978)
Games We Like is a book that explores the psychology, sociology, and personal preferences behind the games people enjoy. It delves into various types of games$1 (Branging from traditional board games to digital experiences$1 (Band examines why certain games capture the imagination and attention of individuals and groups. The book highlights the cultural and emotional factors that influence game choices, offering insight into the evolving nature of gaming preferences across different demographics. By blending theory with personal anecdotes and case studies, the author provides a comprehensive look at the intersection of fun, competition, social interaction, and cognitive engagement in gaming.s